Alimentación Saludable: Baje su presión arterial con DASH - Valerie Weyenberg; Karla P. Shelnutt; Linda B. Bobroff (EDIS, 2010)
FCS8884-Span, a 2-page fact sheet by Valerie Weyenberg, Karla P. Shelnutt, and Linda B. Bobroff, is the Spanish language version of FCS8884/FY1128 Healthy Eating: Lowering Your Blood Pressure with DASH. It outlines an eating plan rich in fruits, vegetables, and low-fat dairy products, that can prevent and reduce high blood pressure. Published by the UF Department of Family Youth and Community Sciences, November 2009.